Pembuatan Ecobrick Sebagai Upaya Pengurangan Sampah Plastik Di SDN Babakan Peundey - Ramadhani, Denisa; Fauzi, Ilman Miftahul; Sa'adah, Silvi; Pipit, Pipit (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Kelurahan Tanjung is one of the villages located in Kecamatan Kawalu, a sub-district located in Tasikmalaya City, West Java, Indonesia. Kawalu is one of the five sub-districts in Tasikmalaya City. Geographically, Kelurahan Tanjung is located in a strategic area, allowing easy access to various important places in Tasikmalaya City as well as to other cities in West Java.In the research the author used a type of qualitative research. The data sources used by the author are primary data and secondary data. Primary data was obtained by interviewing the babakan peundeuy elementary school teachers and the Rw, and the secondary data used were articles, journals, and books related to waste and hygiene materials and related to ecobrik. This community service program activity begins with coordinating with the RW chairman to get permission to carry out community service program activities in RW 01, Tanjung village, especially in the environmental field. After obtaining approval from the head of RW 01, the community service program implementation team carried out the next activity, namely field observations to the Babakan peundeuy Elementary School area. This ecobricks making activity can make students know more about the benefits of waste into items that are worth creativity. Management of plastic waste into ecobrick can produce a useful item in the school environment Dima.